High-performance asymmetric supercapacitor made of NiMoO4 nanorods@Co3O4 on a cellulose-based carbon aerogel - Wang, Meixia; Zhang, Jing; Yi, Xibin; Liu, Benxue; Zhao, Xinfu; Liu, Xiaochan (Beilstein Journal of Nanotechnology, 2020)
In this study, a new nanoporous material comprising NiMoO4 nanorods and Co3O4 nanoparticles derived from ZIF-67 supported by a cellulose-based carbon aerogel (CA) has been successfully synthesized using a two-step hydrothermal method. Due to its chemical composition, the large specific surface and the hierarchical porous structure, the NiMoO4@Co3O4/CA ternary composite yields electrodes with an enhanced specific capacitance of 436.9 C/g at a current density of 0.5 A/g and an excellent rate capability of 70.7% capacitance retention at 5.0 A/g. Moreover, an advanced asymmetric supercapacitor (ASC) is assembled using the NiMoO4@Co3O4/CA ternary composite as the positive electrode and activated carbon as the negative electrode. The ASC device exhibits a large capacitance of 125.4 F/g at 0.5 A/g, a maximum energy density of 34.1 Wh/kg at a power density of 208.8 W/kg as well as a good cyclic stability (84% after 2000 cycles), indicating its wide applicability in energy storage. Finally, our results provide a general approach to the construction of CA and MOF-based composite materials with hierarchical porous structure for potential applications in supercapacitors.
Keywords: carbon aerogel; hierarchically porous structure; nanoporous material; NiMoO4; supercapacitor